Using ALNs to Support a Complete Educational Experience - Melody M. Thompson; Jean W. McGrath (Online Learning, 2019)
The most obvious factor influencing students’ satisfaction with distance learning is convenience of access. While ALNs clearly can provide convenient access to educational content, how do they measure up in terms of access to the broader range of elements that make up a “complete” educational experience?